Pemanfaatan Limbah Sayuran, Buah, dan Kotoran Hewan menjadi Pupuk Organik Cair (POC) di Kelompok Tani Rukun Makaryo, Mojogedang Karanganyar - Catur Rini Sulistyaningsih (Universitas Muhammadiyah Semarang, 2020)
This Community Service is to reduce waste pollution, especially vegetable, fruit and animal waste; and increasing POC production to meet fertilizer needs on agricultural land. The results of community service activities are evaluated on the success indicators of counseling and training, if the post test score has increased ≥ 25% from the pre-test score. Of the 15 participants who took the post test and pre test, none of them had an increase in understanding value below 25%, so that the training and counseling activities reached 100% success indicators with the number of training and service members reaching scores of 2 and 3 totaling 15 people, on average an average increase of 42.46%.